The Contribution of Occupation to Children’s Experience of Resilience - Bowden, Linda (Auckland University of Technology, 2017)
This qualitative descriptive study explored what occupations children aged 10-13 years participate in and how participation in occupation contributes to resilience from their perspective. Little is known about what occupations contribute to resilience, and less is known from children’s perspectives. Exploring how participation in occupation contributes to resilience is important as children in Aotearoa continue to face adverse situations; resilience may help protect their development against uncertainty. The literature available on the definition of resilience was explored from a historical and contemporary perspective, as well the development of resilience in children. Occupation, and children’s participation in occupation literature was reviewed identifying a gap between participation in occupation and building resilience in children. The assumption underpinning this study is that there is a connection between engaging in occupation and building resilience in children. This study utilised a qualitative descriptive methodology to investigate the research questions “what occupations do children aged 10-13 years participate in? and how does their participation contribute to resilience?” Eight participants (four male and four female) were recruited through intermediate schools in Central and South Auckland. Individual semi structured interviews and one focus group was conducted to gather data. The interviews and focus group were audio recorded and later transcribed. A process of thematic analysis, developed by Braun and Clarke (2006) was utilised to analyse the data. Three main themes emerged from this data, they were: what resilience is, occupations children do and how those occupations contribute to resilience and thirdly; and building participation and resilience. The study revealed sophisticated descriptions of what resilience meant to the participants from their experience, which included the ideas of bouncing back and staying strong. The participants also described what occupations they participate in (using social media, listening to music, active occupations, talking with others, and creative occupations) and how these occupations connect to resilience. The participants in this study described their experience of how participation in those occupations helped them to build resilience by fostering support, letting go, experiencing distraction, and experiencing fun and happiness. Key messages from the findings in this study are that participants identify resilience as bouncing back and staying strong through challenging situations, and that participation in occupation helps to build resilience. The findings suggest that health professionals, policy makers and educators have much to learn from children. Specifically, the need for children to participate in occupations as a way to build resilience. This indicates that a more child-focussed approach is needed to incorporate the perspective of children in practice and policy development. Practitioners working with children could utilise the findings of this study by incorporating participation in occupation in social, health and education intervention plans with children, as well as using occupation based coping strategies when teaching children skills to manage challenges in life. The findings also suggest that the education of those who engage with children such as teachers and health professionals need to understand how important participation in occupation is to children, and gain insight into children’s perspectives about how resilience is developed in order to influence health and wellbeing of children.
Keywords: Qualitative descriptive; occupation; resilience; children